Women leadership and issues of female-headed households in Kedak Village, Kediri Regency - Kristiani Samosir; Juwita Hayyuning Prastiwi (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
This research discusses women's leadership and the issue of female-headed households in Kedak village, Kediri regency, with the background that 20 percent heads of households in the village are women, and led by a female village head who is also female-headed households. This research aims to analyse the role and impact of Sunarti's leadership on the issues faced by female headed-households in Kedak Village. This research fills the gap in the literature on women's leadership in rural areas and provides information about policies and programs that are responsive to female-headed households. By using a feminist research methodology that practices qualitative methods with data collection techniques such as literature study, document study, and interviews, this research concludes three things, firstly, socio-political pressure of community and Sunarti's leadership experience are the main factors in obtaining her position. Secondly, women's representation in Kedak Village government is still less than half of male representation. Third, Sunarti's efforts to accommodate the issues of female-headed households are reflected in the economic, health, and political sectors. Although not yet optimal, Sunarti's leadership shows partiality towards female-headed households.